My online privacy for seniors - Rich, Jason (quepublishing.com - online publishing. AARP, QUE, 2019)
My Online Privacy for Seniors is an exceptionally easy and complete guide to protecting your privacy while you take advantage of the extraordinary resources available to you through the Internet and your mobile devices. It approaches every topic from a senior's point of view, using meaningful examples, step-by-step tasks, large text, close-up screen shots, and a custom full-color interior designed for comfortable reading. --
Online security basics -- Safely surf the Internet -- Protect your security when working with emails -- Handling online banking tasks securely -- Protect your privacy and security when shopping online -- Use social media safely -- Protect your privacy when publishing and sharing photos online -- Safely store data, documents, and files in the Cloud -- Customize the security settings on your smartphone or tablet -- Glossary.
Includes index
"User level: beginning-intermediate"--Back cover.
108913
Keywords: Internet -- Security measures; Computer security; Data protection; Internet and older people; Technology and older people; Technology and the elderly; Computers and older people; Computer networks -- Security measures; Privacy, Right of